No cats in the library (A Paula Wiseman Book, Simon & Schuster Books for Young Readers, 2024)
Clarisse, a street cat who loves books, finds a new home in the library as a read-aloud cat.

Dodo dodgeball (Ready-to-read. Level one Star reader!, ,, 2024)
While the ducks and dodos play dodgeball, Chick sits nearby reading her book.

The secret lives of booksellers and librarians: true stories of the magic of reading (Little, Brown and Company, 2024)
Showcasing the smart and talented people who live between the pages, this inspiring collection of true stories, as told to one of the greatest novelists of our time, invites us into a world where we can feed our curiosities, discover new voices and find whatever we want or require.

You're going to love this book! (Farrar Straus Giroux, 2024)
Publisher Annotation: No, really, you are. It’s got everything you could ever want: comedy, drama, action, heart. Plus―are you ready? It’s got homework! Ahh yeah! And a trip to the best place ever, the dentist! Ahhhh yeahhh! Additionally―brace yourself―it’s got raisins! Nature’s candy. AHH YEAHHH! This book is so great, you won’t be able to stop reading it. I dare you not to have fun.

Welcome to the Hyunam-dong Bookshop (Bloomsbury Publishing, 2024)
Quitting her job and divorcing her husband, Yeong-Ju, in a leap of faith, opens the Hyunam-dong Bookshop, and, welcoming new friends and visitors to her circle, builds an inviting space for hurt and lost souls to rest, heal and learn how to write their own stories.